2017
DOI: 10.1007/s11916-017-0624-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Treatments for Post-Traumatic Headache

Abstract: Factors associated with prognosis in PTH may include the following: severity of TBI, stress, post-traumatic stress disorder, other psychiatric comorbidities, sociocultural and psychosocial factors, litigation, base rate misattribution, expectation as etiology, and chronic pain. There are few high quality studies on the non-pharmacologic treatments for PTH. Thermal and EMG biofeedback appear to have been examined the most followed by CBT. Studies did not have secondary outcomes examining the psychosocial factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…In a randomized controlled trial with patients who had chronic daily headaches of various types, LCT resulted in improved headache ratings and reduced medication use in comparison to avoidance coaching and wait-list control groups. The LCT approach may be especially well-suited to persisting PTH following mild TBI [134]. It has been recently shown that patients with persisting PTH after mild TBI identify a similar pattern of triggers as those in primary headache disorders, but perceive mental exertion as a particularly potent headache precipitant that they try to avoid.…”
Section: Behavioral Treatmentmentioning
confidence: 99%
“…In a randomized controlled trial with patients who had chronic daily headaches of various types, LCT resulted in improved headache ratings and reduced medication use in comparison to avoidance coaching and wait-list control groups. The LCT approach may be especially well-suited to persisting PTH following mild TBI [134]. It has been recently shown that patients with persisting PTH after mild TBI identify a similar pattern of triggers as those in primary headache disorders, but perceive mental exertion as a particularly potent headache precipitant that they try to avoid.…”
Section: Behavioral Treatmentmentioning
confidence: 99%
“…Research supports the use of non-pharmacological treatments for persistent PCH [ [3] , [4] , [5] ]. For example, within the Veterans Affairs/ Clinical Practice Guideline (CPG) for the Management of Concussion and mTBI [ 6 ] the use of “education on lifestyle modifications, PT [physical therapy] [and] integrative medicine techniques (e.g., acupuncture, relaxation therapy, mindfulness training)…” (p.30) for treatment of PCH are recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with migraine are 2-4 times more likely to develop major depressive disorder [13,14]. It is theorized that environmental stressors, work demands, changing sleep cycles and the frequency of traumatic brain injury magnify the burden of headaches and psychiatric conditions [15][16][17][18]. Furthermore, major depressive disorders and pain syndromes have biological associations with levels of thyroid hormones, prolactin and serotonin.…”
Section: Introductionmentioning
confidence: 99%